Micropropagation of Calophyllum brasiliense (Cambess.) from nodal segments - S. S. Silveira; R. Cordeiro-Silva; J. Degenhardt-Goldbach; M. Quoirin (Brazilian Journal of Biology)
Abstract Micropropagation of Calophyllum brasiliense Cambess. (Clusiaceae) is a way to overcome difficulties in achieving large-scale plant production, given the recalcitrant nature of the seeds, irregular fructification and absence of natural vegetative propagation of the species. Cultures were established using nodal segments 2 cm in length, obtained from 1-2 year old seedlings, maintained in a greenhouse. Mercury chloride and Plant Preservative Mixture™ were used in the surface sterilizing stage, better results being achieved with Plant Preservative Mixture™ incorporation in culture medium, at any concentration. Polyvinylpyrrolidone, activated charcoal, cysteine, ascorbic acid or citric acid were added to the culture medium to avoid oxidation. After 30 days of culture, polyvinylpirrolidone and ascorbic acid gave better results, eliminating oxidation in most explants. For shoot multiplication, benzylaminopurine was used in concentrations of 4.4 and 8.8 µM in Woody Plant Medium, resulting in an average of 4.43 and 4.68 shoots per explant, respectively, after 90 days. Indole-3-butyric acid and α-naphthalene acetic acid were used to induce root formation, reaching a maximum rooting rate of 24% with 20µM α-naphthalene acetic acid. For acclimatization. the rooted plants were transferred to Plantmax® substrate and cultured in a greenhouse, reaching 79% of survival after 30 days and 60% after one year.